A genome-wide association analysis reveals new pathogenic pathways in gout - Major, Tanya J; Takei, Riku; Matsuo, Hirotaka; Leask, Megan P; Sumpter, Nicholas A; Topless, Ruth K; Shirai, Yuya; Wang, Wei; Cadzow, Murray J; Phipps-Green, Amanda J; Li, Zhiqiang; Ji, Aichang; et al. (Nature genetics, 2024)
Gout is a chronic disease that is caused by an innate immune response to deposited monosodium urate crystals in the setting of hyperuricemia. Here, we provide insights into the molecular mechanism of the poorly understood inflammatory component of gout from a genome-wide association study (GWAS) of 2.6 million people, including 120,295 people with prevalent gout. We detected 377 loci and 410 genetically independent signals (149 previously unreported loci in urate and gout). An additional 65 loci with signals in urate (from a GWAS of 630,117 individuals) but not gout were identified. A prioritization scheme identified candidate genes in the inflammatory process of gout, including genes involved in epigenetic remodeling, cell osmolarity and regulation of NOD-like receptor protein 3 (NLRP3) inflammasome activity. Mendelian randomization analysis provided evidence for a causal role of clonal hematopoiesis of indeterminate potential in gout. Our study identifies candidate genes and molecular processes in the inflammatory pathogenesis of gout suitable for follow-up studies.
Keywords: Genetic Predisposition to Disease; celogenomová asociační studie; protein NLRP3; jednonukleotidový polymorfismus; Hyperuricemia; Gout; mužské pohlaví; hyperurikemie; Mendelian Randomization Analysis; kyselina močová; mendelovská randomizace; Humans; NLR Family, Pyrin Domain-Containing 3 Protein; Uric Acid; genetická predispozice k nemoci; Genome-Wide Association Study; dna (nemoc); lidé; Male; Polymorphism, Single Nucleotide